Building Hope in Crisis: Global Public Service Broadcaster Innovation During the Covid-19 Pandemic - Sumaiyah, Sumaiyah; Abdullah, Assyari; Jayus, Jayus; Yazid, Yasril; Astuti, Dwi Sutri; Khairi, Akmal; Edison, Edison (Universitas Muhammadiyah Ponorogo, 2025)
This paper aims to explain the role of Public Broadcasting Institutions around the world in delivering accurate and educational information to the public about the Corona virus outbreak which has become a global pandemic. This research uses a literature research approach by collecting various literature such as scientific journals, government reports, NGO reports, and annual reports of Public Broadcasting Institutions. This study uses a qualitative inductive logic-based content analysis method offered by Phillips and Marrying. The findings in this paper illustrate that Public Service Broadcasting, which is a broadcasting institution that must exist in every sovereign country, plays an important role as a public media in reporting, disseminating information, educating and persuading the public to jointly take care of themselves and fight the coronavirus which has become a global pandemic with the following approaches: First, Série Le virus (Senegal) presents drama as a strategy to attract public interest in understand the impact of Covid-19. Second, RAI (Italy) launched a special program called 'Unno Mattina'. Third, the Australian Broadcasting Corporation (ABC) adopts a factual approach in reporting the Coronavirus by relying on verified information. In addition, ABC also broadcasts news and information about the development of the Corona virus with a very high volume. Fourth, the Korean Broadcasting System (KBS) provides reliable information through the operation of the Integrated News Room service for 24 hours a day for COVID-19 since March 4, 2020. The main goal is to provide complete, trusted, and in-depth information to citizens. Fifth, CBC Radio (Canada) aired the series 'The Current' which explains the social and economic impact of the Corona virus in daily life.